(3 cos x + 7) (-2 sin x - 1) = 0

Asked by md reyaj | 1st Aug, 2010, 01:11: PM

Expert Answer:

Dear Student,
In the given problem, the left hand side can only be equal to zero when either one of the two expressions are zero or both of them are zero.
Hence, if the first expression is zero, then
3cosx + 7 = 0
=> cosx = -7/3
However, we know that the range of values that cos function can attain are from -1 to 1. Therefore, cosx can not attain -7/3 value for any value of x. So, the first expression can not be zero for any value of x.
If the second expression is zero, then
- 2sinx - 1 = 0
=> sinx = -1/2
=> x = sin-1(-1/2)
We know that sin attains negative values in third and fourth quadrant. hence, the possible values of x can be (180o + 30o) or (360o - 30o).
Therefore, the value of x can be either 210o and 330o.

Answered by  | 1st Aug, 2010, 02:48: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.